Literature Review on Pedagogical Skills, Technology, and Digitalization - Alif Ringga Persada; A. Sobandi (International Journal of Education and Humanities, 2023)
The purpose of this study is to present an overview of the literature review related to pedagogical knowledge, technology, and digitalization. The method used in this research is qualitative research, where descriptive analysis of existing literature is carried out. The data sources used in this study are journal articles on pedagogical knowledge, technology, and digitalization, the results of which show that pedagogical knowledge plays an important role in the utilization of technology and digitalization in the classroom context. The literature review emphasized that a strong understanding of the principles of effective education and pedagogy is a necessary foundation for educators to integrate technology and digitalization into their classroom practices. With the help of pedagogical information, it enables educators to plan practical learning experiences using technological tools that are appropriate to students' needs and characteristics.  In addition, literary research also shows that technology and digitalization can provide great benefits in an educational context. Appropriate use of technology can increase student engagement, encourage active and collaborative learning, and improve access to educational resources. Moreover, digitization can also change the way educators manage and assess learning. With the help of these articles, the relationship between pedagogical knowledge, technology, and digitalization in educational contexts can be further explored. The purpose of this study is to describe the literature on research on pedagogical knowledge, technology, and digitalization. The method used in this research is qualitative research, where a descriptive analysis of the literature review is conducted. Journal articles related to pedagogical knowledge, technology, and digitalization were used as data sources. The results of this study indicate that there are 24 articles that serve as literature research and can be used as references in the study of pedagogical skills, technology and digitalization